Legal support for the use of natural therapeutic resources in sanatorium and resort treatment of the population - Сидор, Вікторія Дмитрівна; Сидор, В. Д.; Сидор, Виктория Дмитриевна; Sydor, Viktoriia D.; Костицький, Василь Васильович; Костицький, В. В.; Костицкий, Василий Васильевич; Kostytsky, Vasyl V.; Костицька, Ірина Олександрівна; Костицька, І. О.; Костицкая, Ирина Александровна; Kostytska, Iryna O. (Zaporozhye State Medical University, 2019)
The aim. To conduct a comprehensive study of the legal regulation peculiarities of natural therapeutic resources and factors of sanatorium and resort treatment for the population, to identify problems of legal regulation of these relations and to outline the ways to resolve them. Materials and methods. The research material is a modern regulatory framework. The methods of information retrieval, analysis, systematization and generalization were carried out. Results. It has been established that natural therapeutic resources include mineral and thermal water, medical mud and ozokerite, sea and lake brine, sea water, natural objects and complexes with favorable climatic conditions. It has been substantiated that sanatorium and spa treatment is an important part that provides continuity and complexity of medical rehabilitation measures. The main resorts, located on the territory of Ukraine, have been described. It has been determined that regulation of social relations in the sphere of organization and development of resorts and sanatorium-resort treatment, detection and accounting of natural medical resources, ensuring their rational extraction, use and protection in order to create favorable conditions for treatment, medical rehabilitation, prevention of diseases and vacation for people is provided by environmental, land, health care and resort legislation. Conclusions. Legal regulation of the natural therapeutic resources usage is ensured by environmental, land, health care and resort legislation. The purpose of this legislation is to regulate social relations in the sphere of organization and development of resorts and sanatorium and spa treatment, to detect and account natural medical resources, to ensure their rational extraction, use and protection in order to create favorable conditions for treatment, medical rehabilitation, prevention of diseases and population health improvement. Efficient exploitation of natural therapeutic resources in resort treatment is currently affected by a number of economic, political, environmental problems, which have to be solved by organizational and legal means of the state impact on such legal relations.

Мета роботи – здійснити всебічне вивчення особливостей правового регулювання природних лікувальних ресурсів, факторів санаторно-курортного лікування населення, виявити проблеми правового регулювання означених правовідносин та окреслити шляхи їхнього вирішення. Матеріали та методи. Матеріал дослідження – сучасна нормативно-правова база. Використані методи інформаційного пошуку, аналізу, систематизації та узагальнення. Результати. Встановили, що до природних лікувальних ресурсів належать мінеральні й термальні води, лікувальні грязі та озокерит, ропа лиманів та озер, морська вода, природні об’єкти, комплекси зі сприятливими для лікування кліматичними умовами. Обґрунтували, що санаторно-курортне лікування – важлива частина, що забезпечує безперервність, наступність і комплексність лікувальних реабілітаційних заходів. Cхарактеризовано основні курорти, котрі розміщені на території України. Визначено, що регулювання суспільних відносин у сфері організації, розвитку курортів і санаторно-курортного лікування, виявлення та обліку природних лікувальних ресурсів, забезпечення їх раціонального видобутку, використання та охорони з метою створення сприятливих умов для лікування, медичної реабілітації, профілактики захворювань та відпочинку людей забезпечується екологічним, земельним законодавством, законодавством про охорону здоров’я та про курорти. Висновки. Правове регулювання використання природних лікувальних ресурсів забезпечується екологічним, земельним законодавством, охороною здоров’я та курортів. Метою цього законодавства є регулювання суспільних відносин у сфері організації та розвитку курортів і санаторно-курортного лікування, виявлення, облік природних медичних ресурсів, забезпечення їхнього раціонального видобутку, використання та охорони з метою створення сприятливих умов для лікування, медичної реабілітації, профілактики захворювань та оздоровлення людей. Ефективне використання природних лікувальних ресурсів у санаторно-курортному лікуванні населення нині має низку серйозних проблем економічного, політичного, екологічного характеру, що мають бути вирішені за допомогою організаційно-правових заходів державного впливу на зазначені правовідносини.
Kostytsky V. V. Legal support for the use of natural therapeutic resources in sanatorium and resort treatment of the population / V. V. Kostytsky, V. D. Sydor, I. O. Kostytska // Zaporozhye Medical Journal. - Zaporozhye State Medical University, 2019. - Vol. 21. - Issue 6. - Р. 802-807.
Keywords: natural therapeutic resources; heals resort mineral water; medical mud; climate; treatment; medical rehabilitation; prevention; природні ресурси; санаторій; мінеральні води; лікувальні грязі; клімат; лікування; медична реабілітація; профілактика; Research Subject Categories::LAW/JURISPRUDENCE